Eulophidae novae germanicae (Hymenoptera: Chalcidoidea). - Erdös, József (Contributions to Entomology = Beiträge zur Entomologie, 1956)
Nomenclatural Acts Halochariessa Erdös, 1956 (Eulophidae), gen. n. germanica Erdös, 1956 (Halochariessa), spec. n. pannonica Erdös, 1956 (Halochariessa), spec. n.